Surface roughness evaluation of nanofiller composite resin after immersion in 50% calamansi orange juice (Citrus microcarpa) - Viona DIANSARI; Diana Setya NINGSIH; Hafra AMINI (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Nano-filled composite resin is a composite resin that has nano-sized fillers. This filler sizegives an aesthetic appearance to the composite resin thus resembles natural teeth. However, compositeresin has a disadvantage in its polymer matrix, which is easily degraded by acid solutions. Calamansiorange (Citrus microcarpa) is a solution that has acidic properties. The purpose of this research was todetermine the surface roughness value of nanofiller composite resin after immersed in a 50%concentration of calamansi orange (Citrus microcarpa). Ten cylindrical specimens of nano-filled compositeresin (Filtex Z350 XT 3M ESPE), with 5 mm diameter and 2 mm thickness. The specimens wereimmersed for 14 days with the provisions of 5 minutes in the juice of calamansi orange and 23 hours 55minutes in distilled water. Calamansi orange juice is replaced every day. The evaluation of surfaceroughness of specimens before and after immersion using Atomic Force Microscopy (AFM).Furthermore, the data were analyzed using paired t-test with a significant value is p 0.05. The resultsshowed an increase in the average value of surface roughness which was significant after exposure inthe calamansi orange with 50% concentration. KEYWORDS: Atomic Force Microscopy, Citrus microcarpa), surface roughness, .nanofilled composite